Grande sertão: inovação social e promoção da sociobiodiversidade - Carla Soares Godinho (2020)
Innovation is a property related to a given medium that is already rich in its own history and its antecedent norms. In this context, the present study aimed to study the phenomenon of social innovation and the promotion of socio-biodiversity of the Grande Sertão Agroextractive Cooperative (CGS), North of Minas. The Grounded Theory (GT) method was used, with a complementary ethnographic approach. The purpose of GT is to generate a theory, based on data, a dense, articulated and systematic rational interpretation, capable of accounting for the studied reality. The identified problem was the obstacles to the commercialization and valorization of CGS products, hindering the development and stable economic and social maintenance for the families that make up the cooperative. With the studies of CGS history, as well as its economic, social and cultural needs and aspirations, it was possible to visualize the trajectory, development and perspectives of the members of this cooperative. As central focus of the study, the internal functioning of family farming was observed based on a specific project for the exploitation of buriti oil. Thus, we discussed the cooperative's prospects for leveraging its activities in the market, considering the fact that the family composition determines the variation of work and consumption necessary to guarantee the family's survival, from Chayanov's point of view. This work contributes to the literature and the planning of other agricultural cooperatives by showing that, for agricultural cooperatives to establish productivity goals, analysis of the goals of each individual cooperative family is necessary. The goals of the cooperative's executive directors will not necessarily be the same as for cooperative farmers. Such an analysis is essential for, thus, to have an effective definition of productivity and development goals. In a second step, the development of the CGS oil factory was analyzed. The negative experience of the biodiesel project was verified, which failed due to technical reasons and mismatched expectations between farmers and Petrobras. Once again, there is a failure in planning from the perspective of a family unit in the referred project. Thus, in order to reuse the oil factory already installed at CGS, the buriti oil extraction project was proposed. The development of the buriti oil chain, through CGS, was a fundamental factor for the cooperative's permanence in the region. This oil chain with its local peculiarities, traditional knowledge, as well as the presence of tacit knowledge in the process of obtaining buriti shavings, benefited some communities, which led to new projects and perspectives for the cooperative to grow and innovate, even with difficulties found, such as “lack of interest and organization”, according to the members. Key categories were highlighted in the present study, and, through these categories, which account for the reality studied, an innovation model suitable for CGS was suggested, which is based on the strategy of geographic indication of traditional knowledge (TC). Thus, it is hoped to preserve the rights of TC and add values to the buriti (project that was successful in the execution), then to the oil from these fruits extracted at the CGS factory, facilitating the commercialization and promotion of socio-biodiversity products. For Chayanov, the way to develop the agricultural cooperative and bring advantages to the peasantry is to develop cooperative trade in order to progressively increase its scale and, on the basis of this experience, expand cooperation to the sphere of production. In practical terms, we suggest an alternative to overcome the dissatisfaction of cultural devaluation in the trade of products of socio-biodiversity for the buriti of the Norte Mineira region, which is the desire of farmers and cooperative members. In addition, identify whether this solution will be able to be copied in other contexts and projects, such as prospecting for other oil production, and thus use idle capacity at the CGS plant. With all of the above, the present study finds that, for thedevelopment and perspectives of the family farmers' cooperative, it is necessary to take into account the family unit when proposing new projects and initiatives. The organization desired by the farmers must be achieved by projects that consider the real picture in each production nucleus. The new projects must therefore change the action strategies. The buriti project, which was favored by the wealth of tacit knowledge, should be further explored by CGS and serve as a pillar for other projects.